Effect of Gawn Series Propeller Camber Ratio Variations on Fuel Consumption Using Engine Propeller Matching - Maulana Rakhim; Achmad Baidowi; Mahendra Indiaryanto (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2026)
Propeller blade geometry, particularly the camber ratio, plays a critical role in determining hydrodynamic behavior and fuel consumption in marine propulsion systems. This study investigates the influence of camber ratio variation on the performance of a Gawn Series propeller by applying an Engine–Propeller Matching (EPM) approach. Open-water performance characteristics, including thrust coefficient (KT), torque coefficient (KQ), and open-water efficiency (η₀), were obtained through Computational Fluid Dynamics (CFD) simulations for four camber configurations of 0%, 1%, 1.5%. The numerical model was validated using resistance and open-water test data, yielding deviations below 5% and 3%, respectively, which confirms the reliability of the simulation results. The analysis shows that higher camber ratios generally increase thrust and torque as a result of strengthened pressure gradients and enhanced flow acceleration along the suction side of the blade, with the 1% camber configuration demonstrating the highest efficiency at J = 0.9 (η₀ = 0.596), representing a 3.85% improvement over the baseline. Matching the resulting propeller load curves with the performance envelope of a 2 × 3900 kW engine setup provides insight into optimal operating conditions and specific fuel consumption across the vessel’s working speed range. The 1% camber variant consistently delivers better fuel economy, maintaining safe operating points. Overall, these results underscore the substantive influence of camber modification on propeller hydrodynamics and propulsion efficiency, identifying the 1% camber configuration as the most suitable option for 60-m high-speed vessels based on combined hydrodynamic, fuel, and operational criteria within the EPM framework.